2011
DOI: 10.1007/s10342-011-0489-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of understory vegetation management through liming and sewage sludge fertilisation on soil fertility and Pinus radiata D. Don growth after reforestation

Abstract: Tree-understory competition is one of the most important aspects that control tree growth after reforestation. The relationship between trees and the understory can be modified by improving acidic soils with lime and by fertilisation. This experiment aims to evaluate the effect of soil improvements on the pasture-tree relationship by liming and fertilisation on different dates in a Pinus radiata-reforested area. Both lime and sewage sludge improved soil fertility by increasing Ca and reducing Al in the soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A comparison of the effects of lime and sewage sludge on all soil variables shows that, initially, the effect of lime was greater than that of sewage sludge, which may be because the lime was responsible for higher inputs of Ca than sewage sludge (López-Díaz et al, 2007;Mosquera-Losada et al, 2011b). However, the effects of sewage sludge were similar to those observed by Mosquera-Losada et al (2011c) in silvopastoral systems established with P. radiata D. Don in acidic soils (3.87) receiving much lower inputs of sewage sludge (50 and 100 kg total N ha -1 ), which indicates that sewage has a higher residual effect than lime (EPA, 1994). The residual effects of the limed treatment gradually declined in the years after its application, as evidenced by the fact that, in the first years of the study (1998)(1999)(2000)(2001), pasture production and tree growth were higher in the limed plots than in those not receiving limed treatment (Mosquera-Losada et al, 2001;López-Díaz et al, 2007), which indicates that the nutrient uptake by the trees and the pasture was higher in the limed plots.…”
Section: Discussionmentioning
confidence: 68%
“…A comparison of the effects of lime and sewage sludge on all soil variables shows that, initially, the effect of lime was greater than that of sewage sludge, which may be because the lime was responsible for higher inputs of Ca than sewage sludge (López-Díaz et al, 2007;Mosquera-Losada et al, 2011b). However, the effects of sewage sludge were similar to those observed by Mosquera-Losada et al (2011c) in silvopastoral systems established with P. radiata D. Don in acidic soils (3.87) receiving much lower inputs of sewage sludge (50 and 100 kg total N ha -1 ), which indicates that sewage has a higher residual effect than lime (EPA, 1994). The residual effects of the limed treatment gradually declined in the years after its application, as evidenced by the fact that, in the first years of the study (1998)(1999)(2000)(2001), pasture production and tree growth were higher in the limed plots than in those not receiving limed treatment (Mosquera-Losada et al, 2001;López-Díaz et al, 2007), which indicates that the nutrient uptake by the trees and the pasture was higher in the limed plots.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, the most significant variation in understory vegetation in the forest with sludge addition was the enhancement of coverage [49]. Moreover, in the SS fertilization of forests, it has been demonstrated that the understory biomass is increased [50][51][52]. An obvious observation regarding understory herbs in the Mongolian pine plantation during this study period was that there were significant differences between the SL and CK treatments, especially during summer (Figure 6).…”
Section: Responses Of Plant Growth Performances To Ss Applicationmentioning
confidence: 66%
“…Thus, the negative growth effects of control soil and soil amended with a low SS application rate were likely related to soil nutrient deficiencies. Firstly, the initial C/N ratio was 13.1 which is not enough for nitrification rate to provide an adequate supply of nitrogen to plants ( Mosquera-Losada et al 2011). SS tended to enhance the initial potential mineralization both in stable and labile stable OM pools, which represents an advantage in acidic soils in which coniferous forests induce low organic matter decomposition.…”
Section: Discussionmentioning
confidence: 99%